Dimethyl Fumarate Ameliorates Doxorubicin-Induced Cardiotoxicity By Activating the Nrf2 Pathway - Hu, Xiaoliang; Li, Cheng; Wang, Qian; Wei, Zhixing; Chen, Taizhong; Wang, Yuepeng; Li, Yigang (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is limited in clinical application because of its cardiotoxicity. Oxidative stress and apoptosis are crucial in DOX-induced cardiac injury. Dimethyl fumarate (DMF) is an FDA-approved oral drug with powerful effects to reduce oxidative stress and apoptosis through the Nrf2 pathway. This study was aimed to determine whether DMF can protect against DOX-induced cardiac injury. We used both neonatal rat cardiomyocytes (NRCMs) in vitro and DOX-induced cardiac toxicity in vivo to explore the effects of DMF. The results showed that DMF significantly improved cell viability and morphology in NRCMs. In addition, DMF alleviated DOX-induced cardiac injury in rats, as evidenced by decreased CK-MB, LDH levels, improved survival rates, cardiac function, and pathological changes. Moreover, DMF significantly inhibited cardiac oxidative stress by reducing MDA levels and increasing GSH, SOD, and GSH-px levels. And DMF also inhibited DOX-induced cardiac apoptosis by modulating Bax, Bcl-2 and cleaved caspase-3 expression. Moreover, DMF exerted its protective effects against DOX by promoting Nrf2 nuclear translocation, which activated its downstream antioxidant gene Hmox1. Silencing of Nrf2 attenuated the protective effects of DMF in NRCMs as manifested by increased intracellular oxidative stress, elevated apoptosis levels, and decreased cell viability. In addition, DMF showed no protective effects on the viability of DOX-treated tumor cells, which suggested that DMF does not interfere with the antitumor effect of DOX in vitro. In conclusion, our data confirmed that DMF alleviated DOX-induced cardiotoxicity by regulating oxidative stress and apoptosis through the Nrf2 pathway. DMF may serve as a new candidate to alleviate DOX-related cardiotoxicity in the future.